Three new Glossoscolex (Annelida: Crassiclitellata: Glossoscolecidae) in the truncatus group from the Brazilian Atlantic Forest - Feijoo-Martínez, Alexander; Brown, George G. (Zootaxa, 2023)
Three new earthworm species of Glossoscolex (Glossoscolex) in the truncatus species group (intra-clitellar male pores on segment 17) are described: Glossoscolex araucariaensis sp. nov., Glossoscolex cardosoi sp. nov., and Glossoscolex santarosaensis sp. nov. from the Brazilian Atlantic Forest. The three earthworm species were distinguished based on the shape and position of the copulatory pouches (all species), the shape of the calciferous glands (G. santarosaensis) and by the presence of tubercula pubertatis and seminal vesicles restricted to segment 12 (G. cardosoi). All are endogeic, unpigmented and were found in low abundances in the topsoil (0-20 cm depth) of Araucaria forest and plantations, a lowland grass pasture and a shrubby grassland, respectively, and are known only from their type-localities. A table containing some of the main internal and external morphological characteristics of the 29 species/subspecies of the Glossoscolex truncatus group is provided in order to assist comparisons within species. Glossoscolex grandis ibirai Righi, 1971 is raised to species rank due to longer extent of clitellum and presence of genital markings, compared to Glossoscolex grandis (Michaelsen, 1892); furthermore, a new subgroup (matogrossensis) of Glossoscolex (Glossoscolex) is proposed to accomodate G. matogrossensis Righi, 1984, with intraclitellar male pores in 15/16. Some considerations on the ecological and taxonomic affinities within the truncatus group are presented, but further studies, particularly genetic are needed in order to better assess phylogenetic relationships within Glossoscolex (Glossoscolex) species groups.